DEVELOPMENT OF THOUGHTS ON FINANCING NORMS AND THEIR REALIZATION IN ISLAMIC FINANCIAL PRODUCTS IN ISLAMIC FINANCIAL INSTITUTIONS - Dedy Setiawan (Green Publisher, 2022)
Financing carried out with contracts that are in accordance with the Shari'ah in modern times has now become part of the tradition of Muslims at the time of the apostle. Since the time of the Prophet Muhammad. Practices such as accepting deposited assets, lending money for consumption and business purposes, as well as making money transfers, have been common since the time of the Prophet Muhammad . This study aims to develop ideas about financing norms and their embodiment in Islamic financial products in Islamic financial institutions. The research method used in this research is normative juridical with a statute approach or a norm/law approach. The technique used to collect the data is through literature/library studies. In this type of research is historical research . The result of the research is that there is a change in thinking about the existing financing in Islamic financial institutions, especially in Indonesia, including financing in the profit sharing principle, financing in the lease principle, financing in the sale and purchase principle, and financing for complementary equipment. These 4 financings are the flagship products of Islamic financial institutions in Indonesia.